2010
DOI: 10.1186/1471-2296-11-39
|View full text |Cite
|
Sign up to set email alerts
|

Trends in sexually transmitted infections in the Netherlands, combining surveillance data from general practices and sexually transmitted infection centers

Abstract: BackgroundSexually transmitted infections (STI) care in the Netherlands is primarily provided by general practitioners (GPs) and specialized STI centers. STI surveillance is based on data from STI centers, which show increasing numbers of clients. Data from a GP morbidity surveillance network were used to investigate the distribution in the provision of STI care and the usefulness of GP data in surveillance.MethodsData on STI-related episodes and STI diagnoses based on ICPC codes and, for chlamydia, prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 16 publications
2
58
1
1
Order By: Relevance
“…For example, the number of STI-related episodes reported by GPs increased by 44%, from 664 per 100 000 patients to 955 per 100 000 patients between 2002 and 2007 2. At STI clinics the number of consultations increased from 11 378 in 1996 to 78 062 in 2007 29.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the number of STI-related episodes reported by GPs increased by 44%, from 664 per 100 000 patients to 955 per 100 000 patients between 2002 and 2007 2. At STI clinics the number of consultations increased from 11 378 in 1996 to 78 062 in 2007 29.…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia trachomatis (CT), an obligate intracellular bacterium, is the cause of the most commonly reported bacterial sexually transmitted infection (STI) in the Netherlands 1 2. A population-based study in 2002/2003 reported a CT prevalence of 2.5% and 1.5% in 16–29-year-old women and men, respectively 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these STI care providers or programmes will contribute to CT control, yet a comprehensive assessment of their relative contribution in terms of testing, diagnosis and the populations that they serve is thus far unavailable. Sentinel data from Dutch GPs suggest that GPs diagnose the lion's share of CT cases, with estimates reaching 70% (vs 30% in STI clinics) 7. Data from the National Chlamydia Screening Programme (year 2013) in the UK (15–24 year olds) show that the contribution of GPs seems smaller, accounting for 14% of all positive tests (vs >40% by genitourinary (GUM) clinics) 8.…”
Section: Introductionmentioning
confidence: 99%
“…18 Notably, Woodhall et al 5 reported that 42% of patients among new and recurrent GU medicine cases had attended a GP for GW management prior to attending a sexual health clinic, but did not include these costs in their estimate. The current study estimated that approximately 48,695 GW episodes were seen at a GP.…”
Section: Lanitis Et Al Cost Of Genital Warts In Ukmentioning
confidence: 99%